Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Kemampuan Psikomotorik Peserta Didik Pada Mata Pelajaran PAI di MAN 1 Pamekasan - Abd Mannan; Leli Lestari; Dwi Yanti Margareta; Hendra Maulana (Journal of Teacher Training and Educational Research, 2024)
Psychomotor skills are a prerequisite for achieving success in learning PAI (Islamic Education), as the outcomes of psychomotor learning are a continuation of cognitive and affective learning outcomes, which become apparent when students exhibit certain behaviors or actions according to the meanings in these two domains in daily life. This study employs a quantitative approach. The aim of this research is to determine whether there is an effect of the Teams Games Tournament (TGT) learning model on students' psychomotor skills in PAI subjects at MAN 1 Pamekasan. The study uses a quantitative approach. Data collection techniques involve using questionnaires to gather information on the TGT learning model and students' psychomotor skills. Data are analyzed using the product-moment correlation formula. The results indicate an effect of the Teams Games Tournament learning model on students' psychomotor skills in PAI subjects at MAN 1 Pamekasan. This is evident from the analysis using the product moment formula, which shows that the product moment "r" value of 0.565 falls between 0.41 and 0.70, with a moderate interpretation. This means there is a moderate effect of the Teams Games Tournament learning model on students' psychomotor skills in PAI subjects at MAN 1 Pamekasan, with a sufficient contribution